2012
DOI: 10.1121/1.4757746
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cochlear microphonic to a low-frequency tone embedded in filtered noise

Abstract: The cochlear microphonic was recorded in response to a 733 Hz tone embedded in noise that was high-pass filtered at 25 different frequencies. The amplitude of the cochlear microphonic increased as the high-pass cutoff frequency of the noise increased. The amplitude growth for a 60 dB SPL tone was steeper and saturated sooner than that of an 80 dB SPL tone. The growth for both signal levels, however, was not entirely cumulative with plateaus occurring at about 4 and 7 mm from the apex. A phenomenological model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
(35 reference statements)
1
27
0
Order By: Relevance
“…The response, however, is still dominated by basal hair cells near the electrode, which can confound an attempt to measure outer hair cell (OHC) health at the apex of the cochlea (Dallos, 1969; Patuzzi et al, 1989). To solve this problem, Chertoff et al (2012, 2014) implemented a filtered noise paradigm in which 733 & 762 Hz tone stimuli were embedded in high-pass filtered noise with seventeen consecutively increasing cutoff frequencies, allowing them to measure a cumulative response from seventeen corresponding regions along the length of the cochlear partition. Taking into account the electric field decay and geometric distance from each point of measurement to the electrode, they modeled a growth function of the CM amplitude as a function of distance along the length of the cochlear partition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response, however, is still dominated by basal hair cells near the electrode, which can confound an attempt to measure outer hair cell (OHC) health at the apex of the cochlea (Dallos, 1969; Patuzzi et al, 1989). To solve this problem, Chertoff et al (2012, 2014) implemented a filtered noise paradigm in which 733 & 762 Hz tone stimuli were embedded in high-pass filtered noise with seventeen consecutively increasing cutoff frequencies, allowing them to measure a cumulative response from seventeen corresponding regions along the length of the cochlear partition. Taking into account the electric field decay and geometric distance from each point of measurement to the electrode, they modeled a growth function of the CM amplitude as a function of distance along the length of the cochlear partition.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the electric field decay and geometric distance from each point of measurement to the electrode, they modeled a growth function of the CM amplitude as a function of distance along the length of the cochlear partition. This growth function was deemed the cumulative amplitude function (CAF), and they showed that damage to OHCs will alter the growth of this function (Chertoff et al, 2012, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Considering the origins of gross measurements can help interpret our finding of limited asymmetry. The electro-anatomy of the cochlear spiral generates a complex electric field, and a source does not simply propagate longitudinally toward a round window electrode (Chertoff et al, 2012). Responses from multiple origins with various phases, including those from outer hair cells, inner hair cells, the lateral wall, synapses, and auditory nerve fibers are summed vectorially in gross electrophysiologic measurements.…”
Section: A Harmonic Analysis Applied To Cochlear Responsesmentioning
confidence: 99%
“…Therefore, a tone burst without noise masking may not be place-specific, although it may be frequency-specific based on the frequency spectrum of the stimulus. Using high-pass noise, low-frequency place-specific CMs was in fact recorded in a study on humans (Ponton et al 1992) and supported by a study on animals (Chertoff et al 2012).…”
Section: Limitations For the Use Of Cmwsmentioning
confidence: 98%